Oscillation Criteria for Even-Order Half-Linear Functional Differential Equations with Damping - Shouhua Liu; Quanxin Zhang; Li Gao (Institute of Advanced Engineering and Science, 2014)
In this paper, a class of even-order half-linear functional differential equations with damping is studied. By using the generalized Riccati transformation and the integral averaging technique, six new oscillation criterias are obtained for all solutions of the equations. The results obtained generalize and improve some known results.